Effect of aneurysmatic artery on blood flow having permeability in human organ (Journal of Naval Architecture and Marine Engineering, 2021)
Blood flow in a double aneurysmatic artery of the normal tissue is studied. A Finite Element method is used to analyze numerical simulation of blood flow through aneurysmatic arteries. The Newtonian, generalized Newtonian, Oldroyd-B and generalized Oldroyd-B models are considered due to the behavior of blood viscosity. In this paper, the effect of aneurysmatic artery on blood flow with permeability in human organ has been investigated. The non-Newtonian models have been applied to study the blood velocity, pressure, and wall shear stress in an aneurysmatic artery. A set of partial differential equations are transformed into dimensionless equations using non-dimensional variables and solved numerically. We have focused our consideration on the simulation of blood velocity and pressure in terms of blood flow rate for various Weissenberg numbers (Wi) and Peclet numbers (Pe). The important effects on blood flow of aneursymatic artery for blood velocity, pressure and wall stress profiles are presented graphically for Newtonian and non-Newtonian models.